Copyright Infringement in Youtube Under Indonesian and Malaysian Laws: The Cases of Aisyah Istri Rasulullah and Karna Su Sayang Songs - Sitti Nabila; Sanusi Bintang (Syiah Kuala Law Journal, 2021)
This study describe the prescription problems in the case of Aisyah Istri Rasullullah song constitute infringement under Indonesian Copyright Law No. 28 of 2014 on Copyright; Karna Su Sayang song constitute infringement under Malaysian Copyright Law Act 332 1987 and the implementation of the law regarding the dispute settlement of the Aisyah Istri Rasulullah song and Karna Su Sayang song. The normative legal research method was used in this research. The results of this study shows that the Aisyah Istri Rasulullah song ingfrings Article 5 and 9 Indonesian Copyright Law stipulate that is prohibited to take the advantage of the copyright work without the owner permission and use it for commercial and Karna Su Sayang song infrings Section 13 and 36 Malaysian Copyright law; There are many similarities between the infringing copy and original work, there is a causal relationship between the infringing work and original works, and the infringing is an essential part of the original work. The recommendation for Indonesia’s and Malaysia’s lawmakers is to revise the Copyright law, so that the copyright infringement on YouTube related the use of fair use and pirates from uploading content will get the strengthen sanction. And create more comprehensive policy regarding the protection of song and Music in YouTube to made the enforcement of the policy to become more effective.